Improving Water Supply Systems’ Resilience Variables Using The Fuzzy Delphi Method (FDM) - R Hari Yuliandra; Nurhamidah Nurhamidah; Puti Sri Komala; Vera Surtia Bachtiar (Universitas Andalas, 2026)
This study examines the resilience variables of urban Drinking Water Supply Systems (WSS) in responding to floods, with a focus on West Sumatra Province, Indonesia, using the Fuzzy Delphi Method (FDM). The study identifies three main resilience properties: robustness, recovery, and learning, within a temporal framework. Thirteen sub-properties and 41 indicators were validated using FDM by 10 experts in fields relevant to the research topic. As a result, 12 sub-properties were accepted by expert consensus, while one sub-property, namely governmental situation awareness, was rejected because all three of its indicators failed to meet the validation criteria. A total of 33 out of 41 indicators were considered significant, relevant, and useful by the expert panel. Furthermore, the findings emphasize the critical role of the governmental dimension in determining the resilience level of SPAM in West Sumatra Province. These results will serve as a guide for policymakers in prioritizing resilience-based decisions to mitigate flood threats.